Molecular and neural bases underlying roles of BDNF in the control of body weight - Vanevski, Filip; Xu, Baoji (Frontiers in Neuroscience, 2013)
Brain-derived neurotrophic factor (BDNF) is a potent regulator of neuronal development and synaptic plasticity that is fundamental to neural circuit formation and cognition. It is also involved in the control of appetite and body weight, with mutations in the genes for BDNF and its receptor, TrkB, resulting in remarkable hyperphagia and severe obesity in humans and mice. Recent studies have made significant progress in elucidating the source, action sites, and regulatory pathways of BDNF with regard to its role in the control of energy homeostasis, and have shed light on the relationships between BDNF and other molecules involved in the control of body weight. Here we provide a comprehensive review of evidence from pharmacological, genetic and mechanistic studies, linking BDNF to the control of body weight. This review also aims to organize the main findings on this subject into a more refined framework and to discuss the future research directions necessary to advance the field.